STRATEGI POLITIK CALON LEGISLATIF MUDA DALAM PEMILIHAN UMUM DPRD KOTA PEKANBARU TAHUN 2024 - Akbar, Finoriza Syahputri; ', Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The 2024 general election is a simultaneous general election to elect the President & Vice President, Members of the DPR, DPD, Provincial DPRD and Regency/City DRPD. Since 2019-now, the participation of the younger generation as voters and even participants has increased. Young legislative candidates, abbreviated as young legislative candidates, are entering the election to bring a new color to the world of politics, where elections are usually attended by candidates who have been involved in politics for a long time. It is proven that currently many young legislative candidates are taking part in the elections. The aim of this research is to find out what the political strategy of young legislative candidates is in the 2024 Pekanbaru City DPRD general election. As well as finding out what factors influence the political strategy of young legislative candidates in the 2024 Pekanbaru City DPRD general election. The method used in this research is a qualitative method with a descriptive approach, the research location is in the environment of young legislative candidates. This research uses two types of data, namely primary data and secondary data. Data collection techniques were obtained through interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and finally drawing conclusions. The findings obtained in this research are the that succes of offensive and defensive strangies is greatly influenced by the ability to integrate social, political, economic capital as well as the use of social media and techonology, affective communication. Keywords: Young legislative candidates, Political strategy, Elections.